Leveraging Telemedicine for Quality Improvement Video Review of Critical ICU Events: A Novel Multidisciplinary Form of Education. (10th September 2021) - Gold, Andrew K.; Huffenberger, Ann; Lane-Fall, Meghan; Pascual Lopez, Jose L.; Rock, Kristen C.
Abstract : Objectives: The objectives of this study were to codify the events triggering bedside recording and to report the types of performance issues identified that were then used to inform dedicated ICU quality improvement efforts. Design: This is a retrospective descriptive analysis of a video review program conducted at a single institution from July 2016 to November 2019. Setting: Surgical and Trauma ICU at a single urban academic quaternary care center. Patients: All patients admitted to the surgical and trauma ICU between July 2016 and November 2019 were eligible for the study as all ICU beds in our health system institutions are equipped with closed circuit video/audio monitoring. Through an institutional review board approved program, any event triggering the immediate bedside presence of a provider in the ICU is routinely recorded at the discretion of the care team or tele-intensivist. Interventions: A database of these events was created over a 3-year period, and cases were reviewed for content, quality improvement, and educational opportunities. Select recordings were analyzed and shared at multidisciplinary/multiprofessional video review sessions. Measurements and Main Results: There were 286 critical events video recorded and reviewed in the ICUs between July 2016 and November 2019. The most commonly recorded events included: cardiopulmonary arrests ( n = 75), intubations ( n = 71), and acute clinical decompensation triggered by nonreassuring vital signs ( n = 57) or arrhythmias ( n = 13). Of these recordings, 59 were shared at video review conferences, where quality of care was assessed and thematic opportunities for improvement were characterized. Recurrent quality improvement themes that were identified included adherence to protocols, the importance of teamwork and closed-loop communication, clearly designated team leadership, and the use of universal precautions. Conclusions: Video review in the ICU is feasible and presents valuable opportunities for quality improvement and educational discussions.